(untitled) (Global Journal of Science Frontier Research, 2019)
The genus Cinnamomum consists of more than hundred species which occur in Asia and Australia. Cinnamon bark oil possesses a sweet and strong taste. It is employed in food and flavoring industry. Cinnamon has antimicrobial, antidiabetic, antiulcer and anti-inflammatory properties. In this study, cinnamon bark oil was extracted from whole cinnamon bark and powdered cinnamon by hydrodistillation. Whole cinnamon, powdered cinnamon, and market cinnamon oils, analyzed by using GCMS, showed variation in the chemical composition. Data from the current study was compared with cinnamon bark oil composition from five different countries, obtained from the literature survey.